Production of PDMS/PEG-PVDF thin film composite membrane for CO2/N2 separation - Siti Khadijah, Md Esa (2012)
A thin film composite (TFC) membrane was prepared for separation of carbon dioxide (CO2) and nitrogen (N2). The support layer was fabricated from different concentrations of polyethylene glycol (PEG) and the coating layer was prepared from different concentration of polydimethylsiloxane (PDMS). The concentration ratio of PDMS to PEG is 2:1, 1:1 and 1:2.Permeances and selectivity of the prepared membranes CO2 and N2 gases and their mixtures were measured under trans membrane pressure of 1 bar. The different concentration ratio of PDMS to PEG plays an important role for permeability and selectivity of CO2/N2 gas separation.It was shown that the highest permeability and selectivity was belong to membrane coating ratio of 1:2 (PDMS: PEG) followed by 2:1 (PDMS: PEG) and lastly 1:1 (PDMS:PEG).The result of permeation test was supported by the results from SEM and FTIR. SEM showed the membrane morphology for surface and cross section membrane. While, FTIR showed the functional group that exists within molecules in membranes.